2019
DOI: 10.1109/access.2019.2926161
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Multichannel Access in High-Frequency Diversity Networks: A Multi-Agent Learning Approach With Correlated Equilibrium

Abstract: This paper investigates the problem of multiuser multichannel access in distributed high-frequency (HF) diversity communication networks using a game-theoretic learning algorithm which is based on correlation equilibrium (CE). We formulate the channel access problem in the HF networks as a non-cooperative game. In the access game, each user equipment (UE) optimizes its access strategy without the information about other UEs, which makes the channel access problem challenging. It is proved that there is at leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The author in [24] proposed a distributed cooperation policy selection scheme for interference to perform subcarrier assignment for uplink multi-cell OFDMA systems by adopting the correlated equilibrium solution concept that achieves better performance by allowing each user to consider the joint distribution among users' actions to minimize the interference. Also, in [16], the author showed by using a game-theoretic learning algorithm which is based on correlation equilibrium in the problem of multi-user multichannel access in distributed high-frequency diversity communication networks can completely avoid interference and get optimal throughput. Moreover, it also guarantees fairness among all user equipment.…”
Section: Discussion Of Application Scenariosmentioning
confidence: 99%
See 1 more Smart Citation
“…The author in [24] proposed a distributed cooperation policy selection scheme for interference to perform subcarrier assignment for uplink multi-cell OFDMA systems by adopting the correlated equilibrium solution concept that achieves better performance by allowing each user to consider the joint distribution among users' actions to minimize the interference. Also, in [16], the author showed by using a game-theoretic learning algorithm which is based on correlation equilibrium in the problem of multi-user multichannel access in distributed high-frequency diversity communication networks can completely avoid interference and get optimal throughput. Moreover, it also guarantees fairness among all user equipment.…”
Section: Discussion Of Application Scenariosmentioning
confidence: 99%
“…Although few articles tried to apply machine learning with correlated equilibrium solution concept in some applications, there are concerns within their research when applying to real-life scenarios. For example, some research showed that the Q-Learning method [14], [15] could achieve the correlated equilibrium within the system [16]- [18]. However, the issues with the Q-Learning method are high space and power consumption.…”
Section: Introductionmentioning
confidence: 99%